2022
DOI: 10.1039/d2ra02542f
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolone-type compounds: synthesis andin silicoassessment of antiviral potential against key viral proteins of SARS-CoV-2

Abstract: Coronavirus outbreak is still a major public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…An artificial intelligence-driven study has identified ruxolitinib as a promising drug for COVID-19. 48 Other than ruxotinib, several pyrazole-containing moieties have been reported to show anticancer 49 and coronavirus inhibitory 50 effects. Considering these facts and the havoc like situation created by the COVID-19 pandemic throughout the world prompted us to check the theoretical effectiveness of synthesized compounds as drug toward COVID-19 treatment as well.…”
Section: Results and Discussionmentioning
confidence: 99%
“…An artificial intelligence-driven study has identified ruxolitinib as a promising drug for COVID-19. 48 Other than ruxotinib, several pyrazole-containing moieties have been reported to show anticancer 49 and coronavirus inhibitory 50 effects. Considering these facts and the havoc like situation created by the COVID-19 pandemic throughout the world prompted us to check the theoretical effectiveness of synthesized compounds as drug toward COVID-19 treatment as well.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In our previous report, 44 twenty pyrazolone derivatives a-t bearing different ring C substitution were synthesised and characterised (Table 1). The crystal structure analysis of compound p revealed the differences between rings A and B, i.e., the existence of pyrazolone and pyrazole moiety.…”
Section: Antioxidant Activity Of Compounds A-t Against Dpph Radicalmentioning
confidence: 99%
“…The crystal structure analysis of compound p revealed the differences between rings A and B, i.e., the existence of pyrazolone and pyrazole moiety. 44 In this work, compounds a-t were subjected to in vitro antioxidant screening using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay (Table 2). This method was selected since it is noted as reliable for the prediction of the radical scavenging activity against reactive oxygen species present in the living cell.…”
Section: Antioxidant Activity Of Compounds A-t Against Dpph Radicalmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Building upon these principles and the growing impact of organocatalysis in the pharmaceutical industry, [38][39][40][41][42] in this manuscript an effective synthetic strategy for the preparation of functionalised b-hydroxy-b-pyrazolone amides in high dr and er (up to >95 : 5 dr, >99 : 1 er) is described. Given that nitrogencontaining heterocycles are incorporated into an array of biologically relevant compounds, [43][44][45][46] and with pyrazole derivatives a prevalent heterocycle of widespread relevance, [47][48][49][50][51][52] the generation of catalytic enantioselective methods that would lead to chiral pyrazolone heterocycle derivatives was targeted. [53][54][55][56] The developed process combines an isothiourea-mediated highly enantioselective formal [2 + 2]-cycloaddition of C(1)-ammonium enolates to generate diastereoisomeric spirocyclic b-lactones, coupled with a subsequent substrate-controlled DyKAT type III process where the absolute conguration at C(3) within the blactone is labile and that at C(4) is xed (Fig.…”
Section: Introductionmentioning
confidence: 99%